The Role of Internal Control and Firm-Specific Characteristics on Firm Value: Evidence from Indian Financial Services Sector - Janardhanan, Anju Kalluvelil; R, Uma V (Indian Journal of Finance and Banking, 2020)
This research determines the role of firm-specific characteristics such as firm size, firm age, liquidity, firm complexity, board independence, institutional ownership, non-performing assets, annual volatility of stock returns, leverage and internal control represented by Enterprise Risk Management (ERM) and Big4 auditor on the firm value measured using Tobin’s Q, Return On Equity (ROE) and Return On Assets (ROA). This proposition is addressed with the sound statistical investigation of 67 companies listed in the NSE financial services sector by utilizing annual panel data for 11 years from 2007-17. The important findings of the study are that the purchasers consider firm size, firm age, liquidity, the volatility of stock returns, and non-performing assets. ROA shows that the management has to focus on firm size, firm age, and volatility of stock returns. ROE informs that the investors will look into firm size, firm age, institutional ownership, non-performing assets, leverage, firm complexity, and volatility of stock returns.